PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR MATA PELAJARAN SBDP MATERI MEMBUAT SOUVENIR DENGAN TEKNIK ANYAMAN SISWA KELAS V SDN 013 MARANGKAYU - Muhammad Ari Sulianto; Muhlis; Usfandi; M.Ramli; Sukriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the decline in learning outcomes of 5th-grade students at SD Negeri 013 Marangkayu in SBdP learning. Based on the problem formulation above, the objective of this research is "to determine the effect of the project-based learning model on students' learning outcomes in the SBdP subject, specifically in making souvenirs using weaving techniques for 5th-grade students at SDN 013 Marangkayu." This type of research is descriptive with a quantitative approach. The subjects of the research consist of 40 students from classes V-A and V-B at SDN 013 Marangkayu. Data collection techniques include observation, interviews, tests, and documentation. The research instruments include a test sheet to measure students' knowledge and an interview sheet. Instrument testing includes validity and reliability tests. Data analysis techniques include normality tests, homogeneity tests, and hypothesis tests. The results of this research include: (1) The pretest was conducted over 2 days at SDN 013 Marangkayu, (2) The posttest was conducted in 1 day in both the experimental and conventional classes, (3) The pretest and posttest results in the control and experimental classes showed that the average score was higher in the experimental class, which was 57-60 compared to the control class, which was 51-75.